2010
DOI: 10.1002/asia.200900585
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State Reversible Geminate A*+B↔C*+D Reaction in Two Dimensions

Abstract: The reversible geminate transfer reaction, A*+B↔C*+D, has been studied in two dimensions. For the excited‐state transfer reaction with two different lifetimes and quenching, the exact analytical Green functions have been generalized for an arbitrary initial condition in the Laplace domain. Long‐time asymptotic behaviors of survival probabilities have been analyzed in the time domain as well as short‐time expressions. The two‐dimensional survival probabilities have been found to show logarithmic decay behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…15,23 We can predict the long-time behaviors of probability functions straightforwardly in the Laplace domain without detailed analysis of three roots i . 36,37 In this way, we find that the long-time behaviors depend on the sign of 3 .…”
Section: ͑37͒mentioning
confidence: 67%
“…15,23 We can predict the long-time behaviors of probability functions straightforwardly in the Laplace domain without detailed analysis of three roots i . 36,37 In this way, we find that the long-time behaviors depend on the sign of 3 .…”
Section: ͑37͒mentioning
confidence: 67%
“…Other kinds of dimensionality reductions can be studied in a similar way. Since more complicated two-dimensional diffusion-influenced reactions were reported, 25,26 these results can be applied to the present problem dealing with different mechanisms. These will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 94%
“…As well as irreversible reactions, 2, 5 various types of reversible reactions for a geminate particle pair have been investigated. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] The partial differential equations describing diffusion processes have been analytically solved and the kinetics at long times has been studied by examining the properties of the solutions. The simplest case, an irreversible A + B → C reaction occurring in the groundstate was solved several decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…43,44,55 The types of reaction have been extended to a ground-state A + B C + D reaction or an excited-state A + B * C * + D reaction. 50,52,56 Some exact solutions were obtained and the analytic properties of these solutions were analyzed. 42,44,50 Specially, from the singularity properties of the solutions, it was shown that the kinetics at long times presents different asymptotic behaviors in various dimensional cases when certain conditions on the parameters such as rate constants, radii of reactants, diffusion constants, or field strengths, are satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation